Particulate matter 2.5 air pollution and low birth weight incidence: a cross-sectional analysis in Jakarta Region - Adzka Fahma Rodliya; Aqila Nurhasanah Harahap; Resa Paksi Mandariska (Indonesian Pediatric Society, 2026)
Background Jakarta is one of the most polluted cities in Southeast Asia, with particulate matter 2.5 (PM2.5) levels frequently exceeding international standards. Exposure to PM2.5 during pregnancy has been linked to adverse fetal outcomes, including intrauterine growth restriction and low birth weight (LBW). Objective To analyze an association between PM2.5 concentration and the incidence of LBW in Jakarta Province, Indonesia. Methods A retrospective cross-sectional study was conducted using secondary data from community health centers (Puskesmas) located within a 5-km radius of Air Quality Monitoring Stations (AQMS) in five regions of Jakarta: Bundaran Hotel Indonesia (HI), Kelapa Gading, Jagakarsa, Lubang Buaya, and Kebon Jeruk. Results A total of 648 LBW cases and 11,498 normal birth weight (NBW) cases recorded in 2020–2021 were included through total sampling. PM2.5 concentration data were obtained from the Jakarta Environmental Agency. Data were analyzed using univariate, bivariate (Pearson’s correlation), and simple linear regression tests. A significant positive correlation was found between PM2.5 concentration and LBW incidence (r=0.885; P=0.049) in 2020, whereas the 2021 data showed no significant correlation (r=0.871; P=0.055). Regression analysis revealed that every one-µg/m³ increase in PM2.5 concentration was associated with a 0.091% rise in LBW cases. Areas with higher pollution levels, particularly Lubang Buaya and Kebon Jeruk, showed the highest prevalence of LBW. Conclusion There was a significant positive correlation between PM2.5 air pollution and the incidence of LBW in Jakarta, particularly in areas with high levels of pollution, based on 2020 data. These findings underscore the importance of implementing public health interventions and enhancing air quality management to safeguard maternal and neonatal health.